1995
DOI: 10.1016/s0969-2126(01)00202-7
|View full text |Cite
|
Sign up to set email alerts
|

Three new crystal structures of point mutation variants of mono TIM: conformational flexibility of loop-1, loop-4 and loop-8

Abstract: The residual catalytic activity of monoTIM can now be rationalized. In the presence of substrate analogues the active-site loops, loop-1, loop-4 and loop-8, as well as the catalytic residues, adopt conformations similar to those seen in the wild-type protein. These loops lack conformational flexibility in wild-type TIM. The data suggest that the rigidity of these loops in wild-type TIM, resulting from subunit-subunit contacts at the dimer interface, is important for optimal catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 34 publications
5
44
0
Order By: Relevance
“…Interestingly, a similar switch of Leu238 and Trp12 was seen in the crystal structure of another unliganded monomeric TIM (monoSS-TIM 23 ), although in this case helix A1 remains intact and loop 1 follows a path somewhat intermediate between the paths of ml1TIM and ml8bTIM (Fig. 4).…”
Section: Structure Of Loopsupporting
confidence: 60%
See 3 more Smart Citations
“…Interestingly, a similar switch of Leu238 and Trp12 was seen in the crystal structure of another unliganded monomeric TIM (monoSS-TIM 23 ), although in this case helix A1 remains intact and loop 1 follows a path somewhat intermediate between the paths of ml1TIM and ml8bTIM (Fig. 4).…”
Section: Structure Of Loopsupporting
confidence: 60%
“…Specifically, it suggests that the buried Leu238 conformation is essential for stabilizing the structure of the monomeric folding intermediate of wildtype TIM, which is known to exist transiently. 28 -31 In this respect, the conformational heterogeneity of loop 1/loop 8 is very similar to the conformational heterogeneity seen for loop 4 in other structures of monomeric TIM: 23 two conformations of loop 4 are observed in structures of monomeric TIM. These structures also interconvert, 23 and one of them, as seen also in dimeric wild-type TIM, is stabilized (in wild-type TIM) by interactions across the dimer interface.…”
Section: Conserved Ala236-ser237-leu238 Sequence Of Loopsupporting
confidence: 56%
See 2 more Smart Citations
“…Via this protocol, a 15-residue stretch (loop-3) of the trypanosomal, glycosomal TIM was changed into an 8-residue stretch. The crystal structures of several of these monomeric TIMs ( Table 1) have shown that the loops involved in dimerisation in wild-type TIM become disordered or adopt nonwild-type conformations (in particular in the unliganded structures) in the monomeric state [33,78]. For example, loop-4 is also seen to adopt a new well-ordered outwardoriented conformation in monoTIM (Fig.…”
Section: The Tim-barrel Foldmentioning
confidence: 98%